Companion Proceedings of the 22nd International Conference on Intelligent User Interfaces 2017
DOI: 10.1145/3030024.3038273
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Conference Attendees with Visual Decision Making Interfaces

Abstract: Recent efforts in recommender systems research focus increasingly on human factors affecting recommendation acceptance, such as transparency and user control. In this paper, we present IntersectionExplorer, a scalable visualization to interleave the output of several recommender engines with user-contributed relevance information, such as bookmarks and tags. Two user studies at conferences indicate that this approach is well suited for technical audiences in smaller venues, and allowed the identification of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Edwards and Veale (2017, 81) point out that machine learning explanations are conditioned by the type of user: any explanation needs to be usable by its audience. Developing a visualization for recommender-system results that reveals some of the origins of its decisions, Verbert et al (2016) found that users, as one might hope, place greater trust in explained than in unexplained results.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Edwards and Veale (2017, 81) point out that machine learning explanations are conditioned by the type of user: any explanation needs to be usable by its audience. Developing a visualization for recommender-system results that reveals some of the origins of its decisions, Verbert et al (2016) found that users, as one might hope, place greater trust in explained than in unexplained results.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%